Patterns of engagement in HIV care during pregnancy and breastfeeding: findings from a cohort study in North-Eastern South Africa - David Etoori; Brian Rice; Georges Reniers; Francesc Xavier Gomez-Olive; Jenny Renju; Chodziwadziwa Whiteson Kabudula; Alison Wringe (BMC, 2021)
Abstract Background Eliminating mother-to-child transmission of HIV (MTCT) in sub-Saharan Africa is hindered by limited understanding of HIV-testing and HIV-care engagement among pregnant and breastfeeding women. Methods We investigated HIV-testing and HIV-care engagement during pregnancy and breastfeeding from 2014 to 2018 in the Agincourt Health and Demographic Surveillance System (HDSS). We linked HIV patient clinic records to HDSS pregnancy data. We modelled time to a first recorded HIV-diagnosis following conception, and time to antiretroviral therapy (ART) initiation following diagnosis using Kaplan-Meier methods. We performed sequence and cluster analyses for all pregnancies linked to HIV-related clinic data to categorise MTCT risk period engagement patterns and identified factors associated with different engagement patterns using logistic regression. We determined factors associated with ART resumption for women who were lost to follow-up (LTFU) using Cox regression. Results Since 2014, 15% of 10,735 pregnancies were recorded as occurring to previously (51%) or newly (49%) HIV-diagnosed women. New diagnoses increased until 2016 and then declined. We identified four MTCT risk period engagement patterns (i) early ART/stable care (51.9%), (ii) early ART/unstable care (34.1%), (iii) late ART initiators (7.6%), and (iv) postnatal seroconversion/early, stable ART (6.4%). Year of delivery, mother's age, marital status, and baseline CD4 were associated with these patterns. A new pregnancy increased the likelihood of treatment resumption following LTFU. Conclusion Almost half of all pregnant women did not have optimal ART coverage during the MTCT risk period. Programmes need to focus on improving retention, and leveraging new pregnancies to re-engage HIV-positive women on ART.